The Lincoln assassination : the evidence - Edwards, William C., 1947-; Steers, Edward, Jr., 1937- (University of Illinois Press, 2009)
On April 22, 1865, Brevet Colonel H. L. Burnett was assigned to head the investigation into the murder of President Abraham Lincoln and the attempted murder of Secretary of State William H. Seward. Burnett orchestrated the collection of thousands of documents for the Military Commission's trial of the conspirators. This deep archive of documentary evidence--consisting of letters, depositions, eyewitness accounts, investigative reports, and other documents--provides invaluable insight into the historical, cultural, and judicial context of the investigation. Only a fraction of the information presented in these documents ever made its way into the trial, and most of it has never been readily accessible. By presenting an annotated and indexed transcription of these documents, this volume offers significant new access to information on the events surrounding the assassination and a vast new store of social and political history of the Civil War era.